2015
DOI: 10.1155/2015/751582
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Phosphoglyceride Crystal Deposition Disease in the Pelvic Soft Tissues Recurring after Initial Surgery

Abstract: Phosphoglyceride crystal deposition disease (PGDD) is a rare disease entity that is characterized by phosphoglyceride crystal deposition that stimulates the formation of masses in soft tissue scars or bones. We report a case of PGDD in the pelvic soft tissues that recurred after initial surgical treatment. A 50-year-old woman was referred to our hospital for the evaluation of pelvic masses that were observed on an abdominal ultrasound. Magnetic resonance imaging (MRI) revealed masses in the pelvic region, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…The histologic findings for phosphoglyceride crystal deposition disease are known to include clustering of macrophages around the crystals and formation of foreign body granulomas. The crystals are 50–150 μm in diameter, appearing as oval pink or blue aggregates on hematoxylin and eosin staining, arranged in corona-like circles [ 3 ]. On polarized light microscopy, the fibrillar crystals appear refractive [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The histologic findings for phosphoglyceride crystal deposition disease are known to include clustering of macrophages around the crystals and formation of foreign body granulomas. The crystals are 50–150 μm in diameter, appearing as oval pink or blue aggregates on hematoxylin and eosin staining, arranged in corona-like circles [ 3 ]. On polarized light microscopy, the fibrillar crystals appear refractive [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The crystals are 50–150 μm in diameter, appearing as oval pink or blue aggregates on hematoxylin and eosin staining, arranged in corona-like circles [ 3 ]. On polarized light microscopy, the fibrillar crystals appear refractive [ 3 ]. The crystals do not dissolve in the usual specimen creation process, but characteristically dissolve in acetic acid, with oxygen gas formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only 10 cases of PGDD have been reported previously, including our case. The available clinical information on these cases is summarized in Table 1 [ 1 – 7 ]. The mean age of patients is 57 (range, 37–76) years.…”
Section: Case Presentationmentioning
confidence: 99%
“…Postoperative follow-up has not revealed any findings suspicious of recurrence in our case. However, there are reports in the literature of recurrence at 4 years after surgery [ 7 ]. Few studies have reported on the process of crystallization and deposition of phosphoglycerides and so the mechanism remains unclear.…”
Section: Case Presentationmentioning
confidence: 99%